1977
DOI: 10.1161/01.res.41.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic cholinergic control of cerebral blood flow in dogs.

Abstract: SUMMARY We studied the effects of cholinergic receptor activation on cerebral blood flow in dogs anesthetized with chloralose. Continuous measurements of cerebral blood flow, arterial and cerebral spinal fluid pressure, heart rate, and respiratory carbon dioxide tension were made during parasympathetic nerve stimulation and during intraarterial infusion of acetylcholine. Multiple samples of arterial and cerebral venous blood were taken before, during, and after cholinergic vasodilation and analyzed for oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 32 publications
1
37
2
2
Order By: Relevance
“…Cranial nerves have been implicated in cerebral vasodilator responses by a number of investigators who have reported either changes in pial vessel size (Chorobski and Penfield, 1932;Cobb and Fine singer, 1932) or in blood flow of various cerebral structures upon stimulation of selected nerves (James et aI., 1969;D'Alecy and Rose, 1977;Pinard et aI., 1979), or who have observed alteration of the basic regulatory responses of the cerebral vascula ture following ablation of such nerves (James et aI., 1969;Ponte and Purves, 1974). However, this evi dence is counterbalanced by reports showing lack of effects of stimulation (Meyer et aI., 1971;Busija and Heistad, 198 1;Linder, 198 1) or ablation (Bates et aI., 1976;Heistad and Marcus, 1976;Hoff et aI., 1977;Traystman and Fitzgerald, 198 1) of the same cranial nerves on cerebrovascular regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranial nerves have been implicated in cerebral vasodilator responses by a number of investigators who have reported either changes in pial vessel size (Chorobski and Penfield, 1932;Cobb and Fine singer, 1932) or in blood flow of various cerebral structures upon stimulation of selected nerves (James et aI., 1969;D'Alecy and Rose, 1977;Pinard et aI., 1979), or who have observed alteration of the basic regulatory responses of the cerebral vascula ture following ablation of such nerves (James et aI., 1969;Ponte and Purves, 1974). However, this evi dence is counterbalanced by reports showing lack of effects of stimulation (Meyer et aI., 1971;Busija and Heistad, 198 1;Linder, 198 1) or ablation (Bates et aI., 1976;Heistad and Marcus, 1976;Hoff et aI., 1977;Traystman and Fitzgerald, 198 1) of the same cranial nerves on cerebrovascular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral vasodilatation accompanying stimula tion of the facial nerve (VII) was originally de scribed by Cobb and Finesinger (1932) and Cho robski and Penfield (1932), and later confirmed by some (James et aI., 1969;D'Alecy and Rose, 1977;Pinard et aI., 1979) and denied by others (Meyer et aI., 1971;Busija and Heistad, 1981;Linder, 1981), leaving open the question of the role of this nerve in cerebrovascular control. Likewise, evidence has been adduced for the existence of cerebral vasodi lator fibers in cranial nerve III (Klosovskii, 1963;Kameyama, 1980).…”
mentioning
confidence: 95%
“…In light of findings that cortical acetylcholine release increases following cortical arousal (Celesia and Jasper, 1966;Szerb, 1967) and that topically applied atropine can at tenuate the cerebral vasodilatation associated with HV -L V shifts (Scremin et aI., 1973), it is possible that a cholinergic, presumably neurogenic, cerebral vasodilatation occurs concomitantly with cortical arousal. This possibility is strengthened by the well-documented existence of a cerebrovascular dilator innervation whose principal transmitter is presumed to be acetylcholine (Lavrentieva et aI., 1968;Iwayama et aI., 1970;Nielsen et aI., 1971;Nielsen and Owman, 1971;Edvinsson et aI., 1972Edvinsson et aI., , 1976Edvinsson et aI., , 1977Kuschinsky et aI., 1974;Toda, 1974;Matsuda et aI., 1976;Hardebo et aI., 1977;D'Alecy and Rose, 1977;Florence and Bevan, 1979;Burnstock, 1980). …”
Section: Hv-lv Shiftsmentioning
confidence: 99%
“…11 For this measurement, the entire venous effluent from the anterior cranial fossa was diverted through the left temporal sinus by occluding the occipital emissary veins, both sigmoid sinuses and the right temporal sinus. Cerebral venous outflow from the anterior cranial fossa was then measured by a Doppler flow transducer secured in a fixed position over the left temporal sinus.…”
Section: Measurement Of Cerebral Blood Flowmentioning
confidence: 99%
“…11 In that study, the amount of blood sodium extracted by the contents of the anterior cranial fossa was measured and compared to the amount extracted by noncerebral tissues. Cerebral venous blood samples were taken simultaneously from the dorsal sagittal sinus and the left temporal sinus.…”
Section: Measurement Of Cerebral Blood Flowmentioning
confidence: 99%